2018
DOI: 10.1186/s12889-018-5266-3
|View full text |Cite
|
Sign up to set email alerts
|

ANDALE Pittsburgh: results of a promotora-led, home-based intervention to promote a healthy weight in Latino preschool children

Abstract: BackgroundLatino preschool children have higher rates of obesity than preschool children from other racial/ethnic groups; however, few effective, culturally appropriate interventions exist targeting this group. The purpose of this study was to test the feasibility of a 10-week, promotora-mediated, home-based intervention to promote a healthy weight in Latino preschool children.MethodsTrained promotoras (community health workers) delivered 10, 90-min weekly interactive and tailored sessions to Latino families l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 43 publications
(41 reference statements)
3
58
0
Order By: Relevance
“…These mostly U.S. interventions have shown some effect on behaviours but no effect on weight-related outcomes (Showell et al, 2013), including in older children (Bleich et al, 2018). Culturally appropriate home-based obesity prevention interventions targeting preschool children that have been implemented by community-based workers have shown promising findings with regard to feasibility and changes in obesity-related behaviours (Haines et al, 2013;Sosa, Parra-Medina, He, Trummer, & Yin, 2016; Taverno Ross, Barone Gibbs, Documet, & Pate, 2018;Yun et al, 2015), with some significant improvements in weight-related outcomes in overweight and obese children (Taverno Ross et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These mostly U.S. interventions have shown some effect on behaviours but no effect on weight-related outcomes (Showell et al, 2013), including in older children (Bleich et al, 2018). Culturally appropriate home-based obesity prevention interventions targeting preschool children that have been implemented by community-based workers have shown promising findings with regard to feasibility and changes in obesity-related behaviours (Haines et al, 2013;Sosa, Parra-Medina, He, Trummer, & Yin, 2016; Taverno Ross, Barone Gibbs, Documet, & Pate, 2018;Yun et al, 2015), with some significant improvements in weight-related outcomes in overweight and obese children (Taverno Ross et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment by disadvantaged socioeconomic groups were based on ethnicity [ 32 35 , 40 43 ] and age [ 32 35 , 42 ]. The ethnic minority groups in question were Hispanics [ 40 , 41 , 43 ], Koreans [ 40 ], Native Americans [ 42 ] and African Americans [ 32 35 ]. McLeish and Redshaw used HIV diagnosis rather than ethnicity as a basis for recruitment, but the large majority of their participants were immigrant women with a Sub-Saharan African background [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study also relied on referrals to the intervention program, but did not specify who were responsible for those referrals [ 39 ]. Taverno Ross et al [ 41 ] reported using promotoras who recruited participants in the study from their own social networks. This was done during community gatherings, through flyers and word of mouth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations